Notarial archives as cultural heritage: a dialogue for society as an expressive charge of identity - Knight Soto, Idarmis; Delgado Knight, Marla Iris (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The notarial file is a reality where documents that corroborate the protocol and reinforce thelegitimacy of the assets to be protected by people, that is, they constitute heritage linked to identity,daily life and culture, demonstrate how these legitimize rights that are built Through the protection of their own assets with values, which represent the culture of the peoples, constitutes the objective of this article, which through methods, legal historical, synthesis analysis, corroborates that through the observation of the Protocol rules For the preservation of archives, they can be declared cultural heritage due to their expressive cultural and identity values, which constitute a paradigm in modernsociety.